Pengaruh Kinerja Sumber Daya Manusia, Kinerja Manajemen, dan Kinerja Permodalan Terhadap Return On Asset (Studi Kasus Pada Bank Umum Syariah 2011-2015) - Yeni Nor Fitriani; Dina Fitrisia Septiarini (Universitas Airlangga, 2017)
The purpose of this study is to determine the effect of human resources, performance management, and performance of return on capital asset towards ROA. This study uses quantitative approach and the sampling technique used is purposive sampling. The samples used in this study are 10 BUSes. The analysis technique used is panel data regression. The results show that partially intellectual capital with iB-VAIC and the level of capital adequacy significantly affect the ROA, while the quality of GCG does not significantly affect ROA. Simultaneous research results show that intellectual capital with iB-VAIC, quality of GCG implementation and the level of capital adequacy significantly affect ROA. Therefore, the management of intellectual capital or resource management with a good knowledge and quality management of GCG supported by sufficient capital to support the operations of the company will be able to increase the ROA of sharia banks.